Respuesta :

Answer:

(1, 2 )

Step-by-step explanation:

Given the 2 equations

3x + 4y = 11 → (1)

x - 2y = - 3 → (2)

Multiplying (2) by 2 and adding to (1) eliminates the term in y

2x - 4y = - 6 → (3)

Add (1) and (3) term by term to eliminate y

5x = 5 ( divide both sides by 5 )

x = 1

Substitute x = 1 into either of the 2 equations and solve for y

Substituting into (1)

3(1) + 4y = 11

3 + 4y = 11 ( subtract 3 from both sides )

4y = 8 ( divide both sides by 4 )

y = 2

Solution is (1, 2 )

By using elimination method, (1, 2) point is the solution to the system of equations.

What is elimination method?

"The elimination method is the process of eliminating one of the variables in the system of linear equations using the addition or subtraction methods in conjunction with multiplication or division of coefficients of the variables."

Given system of equations

3x + 4y = 11...................(1)

x - 2y = - 3.................(2)

By using elimination method, multiply equation (2) with 3.

Equation(2) : x - 2y = - 3

⇒ 3x - 6y = - 9...................(3)

Subtract equation (1) from (3)

⇒ 3x - 6y - (3x + 4y) =  - 9 - 11

⇒ 3x - 6y -3x - 4y = -20

⇒ -10y = -20

⇒ y = [tex]\frac{-20}{-10}[/tex]

⇒ y = 2

Substitute y value in equation (2)

x - 2y = -3

⇒ x -2(2) = -3

⇒ x - 4 = -3

⇒ x = -3 + 4

⇒ x = 1

Hence, (1, 2) point is the solution to the system of equations.

Learn more about elimination method here

brainly.com/question/14619835

#SPJ2